Albumin and Neutrophil-Lymphocyte Ratio (NLR) Predict Survival in Patients With Pancreatic Adenocarcinoma Treated With SBRT. (March 2018) - Alagappan, Muthuraman; Pollom, Erqi L.; von Eyben, Rie; Kozak, Margaret M.; Aggarwal, Sonya; Poultsides, George A.; Koong, Albert C.; Chang, Daniel T.
Abstract : Purpose: To determine if pretreatment nutritional status and inflammatory markers correlate with survival in patients with locally advanced pancreatic adenocarcinoma treated with stereotactic body radiotherapy (SBRT). Materials and Methods: We retrospectively reviewed 208 patients with newly diagnosed, locally advanced pancreatic adenocarcinoma treated with SBRT at our institution from 2002 to 2014. Laboratory values were collected before SBRT, including hemoglobin, platelets, albumin, red blood cell, white blood cell, neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio, and tumor markers CA 19-9 and CEA. Patients were followed every 3 months with computed tomography (CT) and/or positron emission tomography-CT imaging to monitor for local recurrence and overall survival (OS). Results: Median follow-up after SBRT was 7.5 months (interquartile range, 4.6 to 12.0 mo) for all patients. Median OS for patients with NLR>5 compared with NLR⩽5 was 6.9 and 8.5 months, respectively ( P =0.0057). On univariate analysis, receipt of chemotherapy ( P =0.05, hazard ratio [HR]=0.69), increased albumin ( P =0.002, HR=0.64), increased red blood cell ( P =0.05, HR=0.75), increased lymphocyte count ( P =0.002, HR=0.66), decreased CEA ( P =0.01, HR=0.96), and NLR⩽5 ( P =0.01, HR=0.65) correlated with improved OS. On multivariate analysis, higher albumin ( P =0.03, HR=0.70), receipt of chemotherapy ( P =0.007, HR=0.56), and NLR⩽5 ( P =0.02, HR=0.66) correlated with better survival. Conclusions: Preradiotherapy low albumin levels and NLR>5 correlate with decreased survival in patients with locally advanced pancreatic adenocarcinoma treated with SBRT, indicating the prognostic value of systemic inflammatory markers (such as NLR) and a role of nutritional supplementation to improve outcomes in these patients. Further investigation is warranted.